PKM E-Commerce Kampung Keluarga Berencana Desa Mertasinga Kabupaten Cirebon - Odi Nurdiawan; Fidya Arie Pratama; Nining Rahaningsih (Politeknik Negeri Cilacap, 2020)
The partner of the program is the family planning village group, which consist of mostly housewives in Mertasinga village, Gunung jati sub-district, Cirebon district. This partner group has run a business of fish processing including shredded fish, fish meatball and fish nuggets. Problems experienced by partner groups are the absence of official labels from the National Drug and Food Control Agency (BPOM) and halal certification labels in processed fish products as well as a barcode in the group’s products, shredded fish making equipment has been damaged and requires repair and addition, there is not yet any innovation in making products, so that product diversity is limited, low ability of Human Resources (HR) related to management and marketing, low willingness and understanding in the use of information technology as a suggestion to market their products. The solutions that have been implemented in this program are mentoring for the management of certification labels from the National Drug and Food Control Agency (BPOM) and halal certification labels, improvement of shredded fish making equipment, training for innovation in processed fish products, increasing the ability of Human Resources (HR) in the field of management, training in the composition, use, and utilization of information technology as a marketing tool. The target of the program is to increase the target group's ability: Knowledge increases by 90%, Management by 75%, marketing through internet increases by 80% and sales turnover will increase by 60%.